Effect of gibberellic acid on ipomoea batatas regeneration from meristem culture - Dagnino, Denise Saraiva; Carelli, Maria Luiza D.; Arrabal, Rosangela F.; Esquibel, Maria Aparecida (Pesquisa Agropecuaria Brasileira, 1991)
The elongation of the explants is one of the crucial aspects in developing protocols for regeneration of sweet potato from meristem culture. In order to promote elongation and accelerate explant development, gibberellic acid (GA3) was added to the culture medium. Experimental results were strongly influenced by the cultivars employed. The effect of GA3 was to promote multiple shoot growth and elongation of cv. Mãe de Família; on the other hand, the addition of GA3 had no effect on explant growth in cv. Coração Alado.